Incorporation of population and family welfare messages in all training cources being organized by the governmet and non govrrnmental organizations - National Institute of Health and Family Welfare (New Delhi, 1988)
The world population has already crossed the five billion mark and that of India is now around 800 million. On an average, India added every year seven million during 1951-61, ten million in 1961-71, 13 million in 1971-81 and is expected to add about 15 million during 1981-91. If the growth of population in India continues with the current birth rate of 32.4 and death rate of 11.7 per thousand population and infant mortality rate of 95 per thousand live births, on an average, the population will increase by about 19 million per year during 1991-2000. Thereby, about 235 million more people will be added during the next 13 years. (The decadal increase of population is shown in Annexure I.)
Keywords: Family welfare .